A Functional Near-Infrared Spectroscopy Examination of the Neural Correlates of Cognitive Shifting in Dimensional Change Card Sort Task - Li, Hui; Wu, Dandan; Yang, Jinfeng; Xie, Sha; Luo, Jiutong; Chang, Chunqi (Frontiers in Human Neuroscience, 2021)
This study aims to examine the neural correlates of cognitive shifting during the Dimensional Change Card Sort Task (DCCS) task with functional near-infrared spectroscopy (fNIRS). Altogether 49 children completed the DCCS tasks, and 25 children (Mage = 68.66, SD = 5.3) passing all items were classified into the Switch group. Twenty children (Mage = 62.05, SD = 8.13) committing more than one perseverative errors were grouped into the Perseverate group. The Switch group had Brodmann Area (BA) 9 and 10 activated in the pre-switch period and BA 6, 9, 10, 40, and 44 in the post-switch period. In contrast, the Perseverate group had BA 9 and 10 activated in the pre-switch period and BA 8, 9, 10 in the post-switch period. The GLM results afford strong support to the ‘V-shape curve’ hypothesis by identifying a significant decrease-increase cycle in BA 9 and BA 44, the neural correlations of cognitive shifting.